Industrial relations at centre stage: Efficiency, equity and voice in the governance of global labour standards; Industrielle Beziehungen im Mittelpunkt: Effizienz, Fairness und Mitsprache in der Governance globaler Arbeitsstandards - Thomas Haipeter; Markus Helfen; Anja Kirsch; Sophie Rosenbohm; Christine Uÿuk̈ (Industrielle Beziehungen, 2021)
Considering the persistent violation of labour rights, questions arise as to the effectiveness of policy instruments regarding the governance of global labour standards. We adopt an industrial relations perspective to compare three broad categories of policy instruments: state-centred regulation, employer-centred regulation, and transnational industrial relations agreements. To structure our comparison, we adapt Budd and Colvin's (2014) "Efficiency, Equity and Voice (EEV)" framework for conflict handling to the field of global labour governance. We operationalize the efficiency, equity and voice criteria to examine the outcome of policy instruments and process orientation, their scope and coverage, and the opportunities they provide for worker participation and union building. Our comparison shows that each category of instruments has characteristic strengths and weaknesses, and does not suffice on its own to protect global labour standards adequately. This accounts for why, paradoxically, we observe both a proliferation of policy instruments and the persistent violation of labour rights. More research is required to improve our understanding of how different political instruments could be combined, and we conclude by proposing elementary building blocks that improve the governance of global labour standards along global value chains. – – Angesichts anhaltender Verletzungen von Arbeitnehmerrechten entstehen Fragen zur Effektivitaẗ von Politikinstrumenten zur Governance globaler Arbeitsstandards. Aus einer Perspektive der industriellen Beziehungen heraus vergleichen wir dreiKategorien von Instrumenten: staatliche Regulierung, arbeitgebergefuḧrte Regulierung, und transnationale Vereinbarungen zwischen Arbeitgebern und Gewerkschaften. Um unseren Vergleich zu strukturieren, passen wir Budd und Colvins (2014) Analyserahmen zu Effizienz, Fairness und Mitsprache im Konfliktmanagement auf das Gebiet der Governance globaler Arbeitsstandards an. Wir operationalisieren die Kriterien Effizienz, Fairness und Mitsprache, um die Ergebnis- und Prozessorientierung und den Geltungsbereich von Politikinstrumenten, sowie die Mog̈lichkeiten, welche sie fur̈ Arbeitnehmermitbestimmung und den Aufbau gewerkschaftlicher Strukturen bieten, zu erfassen. Unser Vergleich zeigt, dass die Instrumente jeder Kategorie charakteristische Star̈ken und Schwac̈hen haben, und nicht alleine ausreichen, um globale Arbeitsstandards aufrechtzuerhalten. Dies trag̈t zur Erklar̈ung der paradoxen Beobachtung sowohl einer Proliferation von Politikinstrumenten als auch anhaltender Verletzungen von Arbeitnehmerrechten bei. Weitere Forschung ist noẗig, um zu verstehen, wie verschiedene Politikinstrumente kombiniert werden kon̈nen, und wir enden mit einem Vorschlag elementarer Bausteine, welche die Governance globaler Arbeitsstandards in globalen Wertschop̈fungsketten verbessern kon̈nen.
Keywords: F23; F66; J80; M14; 330; Critical pluralism; global labour standards; global framework agreements; multinational companies; ILO; global labour governance; kritischer Pluralismus; globale Arbeitsstandards; globale Rahmenabkommen; multinationale Unternehmen; ILO; Governance globaler Arbeitsstandards